Green supplier selection: a novel fuzzy double frontier data envelopment analysis model to deal with undesirable outputs and dual-role factors. (2017) - Azadi, Majid; Mirhedayatian, Seyed Mostafa; Saen, Reza Farzipoor; Hatamzad, Mahshid; Momeni, Ehsan
In recent years, green movements, governments and institutions have forced many companies to improve their environmental performance. As a result of this growing interest in the environment, many companies have created integrated relationships with their suppliers to present green products and services. In public transportation sector, the evaluation and selection of appropriate green suppliers according to green supply chain management (GSCM) criteria is necessary for the sustainable development of urban transportation system. Among many evaluation selection methods, data envelopment analysis (DEA) is an appropriate method for green supplier selection. In this paper, to select green suppliers, we propose a new fuzzy double frontier DEA model in the presence of undesirable outputs and dual-role factors. A case study is presented to illustrate the applicability of the proposed model.